Recurrent miscarriage: diagnostic and therapeutic procedures : guideline of the DGGG, OEGGG and SGGG (S2k-Level, AWMF Registry Number 015/050) = Diagnostik und Therapie von Frauen mit wiederholten Spontanaborten : Leitlinie der DGGG, OEGGG und SGGG (S2k-Niveau, AWMF-Registernummer 015/050) - Toth, Bettina; Wischmann, Tewes; Kuon, Ruben-Jeremias (Geburtshilfe und Frauenheilkunde, 2018)
Purpose Official guideline of the German Society of Gynecology and Obstetrics (DGGG), the Austrian Society of Gynecology and Obstetrics (ÖGGG) and the Swiss Society of Gynecology and Obstetrics (SGGG). The aim of this guideline was to standardize the diagnosis and treatment of couples with recurrent miscarriage (RM). Recommendations were based on the current literature and the views of the involved committee members. - - Methods Based on the current literature, the committee members developed the statements and recommendations of this guideline in a formalized process which included DELPHI rounds and a formal consensus meeting. - - Recommendations Recommendations for the diagnosis and treatment of patients with RM were compiled based on the international literature. Specific established risk factors such as chromosomal, anatomical, endocrine, hemostatic, psychological, infectious and immunological disorders were taken into consideration.
Gesehen am 26.04.2019